Vertical Chlorophyll-a Concentration Profiles Observed on The Western Coast of Northern Sumatera During the 2017 Northeast Monsoon - Iskhaq Iskandar; Qurnia Wulan Sari; Aan Johan Wahyudi; Afdal; Wijaya Mardiansyah (Science and Technology Indonesia, 2022)
Subsurface chlorophyll-a (chl-a) concentration variability on Sumatera’s Northwestern coast is part of the phytoplankton biomass that supports and enriches the region’s fisheries supplies. During the 2017 northeast monsoon season from 25th November 25 to 11th December, the Ekspedisi Widya Nusantara (E-WIN) collected data from 16 stations. The finding demonstrates a rise in subsurface chl-a concentration as you get closer to the coast. Furthermore, the deep chl-a maximum (DCM) is only found offshore, with depths−3 between 30 to 50 m and chl-a concentrations of 0.07 to 0.25 mg.m. Surface chl-a concentrations near the coast were found to be high, ranging from 0.2 to 0.25 mg.m-3